Coding telephone numbers to avoid "wrong numbers" - Abaya, Efren F. (Philippine Engineering Journal)
"Wrong numbers" are an annoyance for owners of telephones. These incidents are due to several causes, of which the following two may be the most common : (a) pressing the wrong button on a telephone keypad, or (b) misreading a printed or handwritten telephone number. This paper presents two methods for developing numbering plans that will reduce the incidence of accidental wrong numbers when using push-button telephone sets by utilizing an error-detecting code on telephone numbers. It is demonstrated that small telephone numbering plans for 2 digits to 4 digits can be quickly generated by using a weighted code or by exhaustive search. Rotary dial phones are not considered in the paper.